ESTIMATION OF WIND POWER POTENTIAL FOR PASNI, COAST OF BALUCHISTAN, PAKISTAN - Ahmed, M. Akhlaque; Ahmad, Firoz (Journal of Research (Science), 2004)
The study of the prospect of Wind power potential for Pasni has been made from the available meteorological data. For Pasni the peak months are April, May and June. The monthly average wind speed ranges from 4.5 m sec-1 to 8.0 m sec-1 and the maximum extractable wind power was found to be 221 Wm-2 using 1 m diameter. turbine blade. The power out put for slow and fast wind machine have been estimated to see the possibility of its use for water lifting and small scale power generation. Along with this the feasibility of performance of a 20 KW aero- generator was also examined for Pasni.